Migration as good, bad and necessary: examining impacts of migration on staying Himalayan communities affected by climate change - Himani Upadhyay (Humanities & Social Sciences Communications)
Abstract Within the migration system, the seminal Foresight report highlighted that climate change can have significant implications for staying populations. Yet research on this remains limited. This study aims to fill this gap by assessing the impacts of sustained outmigration on staying farmer communities in the Indian Himalayan Region, affected by incremental climate change. Employing an empirical qualitative approach, new data is collected through semi-structured interviews (n = 72). Staying communities describe migration as good, bad, and necessary with the majority (46%) noting negative impacts such as fewer people to do agriculture, abandoned assets, more tasks for women, loss of community, disrupted household structures, mental health implications for the elderly, and disinvestment in public services. While remittances from migration have positive impacts, they are primarily used for meeting everyday needs (81%) and not invested in climate change adaptation. In addition to migration impacts, changing weather patterns, agricultural shifts, and societal transformations further exacerbate the vulnerabilities of staying populations. Without policy support to address these vulnerabilities, the benefits of migration may not effectively contribute to climate change adaptation. The findings here are likely applicable to staying populations in other mountain areas, facing similar pressures from migration and climate change, underscoring the need for targeted interventions to build long-term adaptive capacity.